METHODOLOGY FOR THE USE OF INFORMATION COMMUNICATION TECHNOLOGIES IN THE DISCIPLINE OF PHYSICAL EDUCATION - Xudoynazarova Gullola Mirxojitdinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article has asked about the advantage of establishing the educational process of future physical culture teachers based on Information Communication Technologies.